2014
DOI: 10.4236/as.2014.52017
|View full text |Cite
|
Sign up to set email alerts
|

Model for stock-recruitment dynamics of the Peruvian anchoveta (<i>Eugraulis ringens</i>) off Peru

Abstract: This paper was aimed at reexamining the validity of the results from Cahuin et al. (Estuar. Coast. Shelf Sci. 84, 2009) and identifying a model to describe the stock-recruitment relationship of the Peruvian anchoveta (Eugraulis ringens). Regression analysis was used to determine if density-dependent effects were present. The analysis did not show the existence of any densitydependent effects. It is important to use environmental factors and take observational and process errors into account when attempting to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…In there, only for 3cases (Oct.-Nov., Dec.-Jan., and Jan.-Feb.), the slopes were not significantly different from unity. For other 2 cases (Apr.-May and Aug.-Sep.), the 95% confidence interval of [26] is explained well using the same concept of the fluctuation mechanism proposed in this paper. That is, my concept for the mechanism in population fluctuation coincides well with that by Davidson and Andrewartha [16] and Andrewartha and Birch [27] in that the density-dependent effect is not a key factor or a negligible factor in controlling the population size.…”
Section: Discussionsupporting
confidence: 63%
“…In there, only for 3cases (Oct.-Nov., Dec.-Jan., and Jan.-Feb.), the slopes were not significantly different from unity. For other 2 cases (Apr.-May and Aug.-Sep.), the 95% confidence interval of [26] is explained well using the same concept of the fluctuation mechanism proposed in this paper. That is, my concept for the mechanism in population fluctuation coincides well with that by Davidson and Andrewartha [16] and Andrewartha and Birch [27] in that the density-dependent effect is not a key factor or a negligible factor in controlling the population size.…”
Section: Discussionsupporting
confidence: 63%
“…Therefore, the apparent SRRs for the species will show increasing loops. This can also be seen in the SRRs for anchovies [15], mackerel and other species [16]. On the contrary, for species with a long reproduction cycle, the apparent SRRs will scatter widely and will show anti-clockwise loops with no trend, such as that observed in bluefin tuna.…”
Section: Discussionmentioning
confidence: 87%
“…The difference in the lag periods for the SOI might be attributed to its influence on the spatial distribution of various prey in relation to the different dietary preferences and life stages of the yellowfin tuna in Zone 1, Zone 2 and Zone 3 [30]- [32]. The effect of SOI on small fish species has been previously reported [33] [34]. Lehodey [12] showed that the recruitment of yellowfin tuna was favorable during positive Pacific Decadal Oscillation (PDO) and El Niño events and unfavorable during negative PDO and La Niña events.…”
Section: Discussionmentioning
confidence: 85%